Adsorption of mixed anionic and nonionic surfactants at the hydrophilic silicon surface - Penfold, J; Staples, E; Tucker, I; Thomas, R (2002)
Specular neutron reflectivity has been used to determine the structure and composition of the mixed anionic and nonionic surfactants adsorbed at the hydrophilic silica solid-solution interface. Measurements show that the anionic surfactant sodium dodecyl sulfate (SDS) is adsorbed at the hydrophilic silica surface in the presence of the nonionic surfactant hexaethylene monododecyl ether but has no affinity for the surface in the absence of the nonionic surfactant. The variations of adsorbed amount, composition, and structure of the adsorbed layer are shown to reflect the different affinities of the two surfactants for the hydrophilic surface. At a solution concentration greater than the critical micellar concentration, the adsorbed amount decreases for solutions increasingly rich in SDS, and the surface composition is not consistent with the pseudo phase approximation.